Contra Perceptions Of The Freedom Of Contract Principle In Law No. 2 Of 1960 Concerning Agricultural Products Sharing With The Community Ijon System In The Bonebeach Environment - BAKUNG, Dolot Al Hasni; ABDUSSAMAD, Zamroni; MUHTAR, Mohamad Hidayat (Indonesia Strategic Sustainability, 2022)
Buying and selling is an activity that takes place and is inherent in every society in the State of Indonesia. Therefore, there are many rules that regulate the matter of buying and selling in Indonesia. Agreements made by the community in terms of buying and selling must be clear and have a legal basis because every agreement born of an agreement is bound by law, as stated in article 1338 of the Civil Code (KUHPerdt). Buying and selling also has its own way, including buying and selling in the ijon or ngijon system, namely selling fruit that has not been seen. This research is categorized into the type of empirical normative legal research, it is based on the issues and or themes raised as research topics. Empirical normative legal research uses case studies in the form of products of legal behavior, for example reviewing laws and their application in society.